Bauran Pemasaran Wisata Agro Salak Pondoh Organik di Dusun Ledoknongko, Desa Bangunkerto, Kecamatan Turi, Kabupaten Sleman - Fransiskus Renaldo Hoya; Dian Pramita Sugiarti (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2020)
This research is located at Wisata Agro Salak Pondoh Organik Ledoknongko (WASPOL), Bangunkerto Village that is one of the agritourism in Sleman District, Yogyakarta. The background of the research includes a variety of activity options in WASPOL, Salak Pondoh as a profitable commodity, and there is government support to preserve organic Salak Pondoh varieties. The tourist activities options in WASPOL is about cultivation, enjoy picking the salak and also processing the fruits into any other product in traditional way. Salak Pondoh is a profitable commodity because it can export in large quantities. The objective of this research is to identify the profile of tourists and marketing mix of WASPOL. The data is collected through interviews and observation. The informants are determined by purposive sampling technique. The data is analyzed qualitatively through the process of data reduction, display, and drawing/verification. The results of the study show that, the profile of tourists visiting WASPOL have the same purpose which is to conduct research, this is because there are researchers from various Universities and Schools in Indonesia. Tourists will also be taught how to cultivate Salak Pondoh by Farmers and can immediately pick and eat Salak fruit. The rate of tourists visits has decreased, from 2015 amounted to 3,493 visitors dropped to 2,523 visitors in 2016 with a percentage decrease of 72%, while in 2017 there were 1,278 visitors with a percentage decrease of 50%. The decline in tourist arrivals from 2015-2017 because WASPOL is more focused on the export of Salak Pondoh fruit. The results of the marketing mix analysis at WASPOL are where WASPOL exports Salak Pondoh to various countries such as China, Australia and Cambodia while salak processed products are only sale in souvenir shops in Yogyakarta. The price of salak exported is Rp. 50,000/Kg, while for salak fruit for sale in plantation areas for Rp. 20,000/basket. Salak Pondoh production process is carried out at the home of the farmers’ groups and all who carry out cultivation activities and salak marketing are people who come from Sub Ledoknongko. Salak plantations are neatly arranged and clean from rubbish. WASPOL is promoted through their official blog, sicantikledoknongko.blogspot.com. There are several recommendation to the management of WASPOL as follow: to add the facilities like toilet and signboard, promoting on social media, and if possible make a website that explains about WASPOL and existing tour packages. Keywords: Tourist Profile, Marketing Mix, Agritourism, Salak Pondoh, Ledoknongko Village